Study of a double epi-layers SiC junction barrier Schottky rectifiers embedded P layer in the drift region - 宋庆文 张玉明 张义门 张倩 吕红亮 (Chinese physics B, 2010)
This paper proposes a double epi-layers 4H-SiC junction barrier Schottky rectifier （JBSR） with embedded P layer （EPL） in the drift region. The structure is characterized by the P-type layer formed in the n-type drift layer by epitaxial overgrowth process. The electric field and potential distribution are changed due to the buried P-layer, resulting in a high breakdown voltage （BV） and low specific on-resistance （Ron,sp）. The influences of device parameters, such as the depth of the embedded P＋ regions, the space between them and the doping concentration of the drift region, etc., on BV and Ron,sp are investigated by simulations, which provides a particularly useful guideline for the optimal design of the device. The results indicate that BV is increased by 48.5% and Baliga＇s figure of merit （BFOM） is increased by 67.9% compared to a conventional 4H-SiC JBSR.